Bedtime Stories in the Industry 4.0 Era: A Descriptive Study of Parents’ Practices and Perceptions in Pontianak - Siska Perdina; Puja Maulidia (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the relevance of bedtime stories in early childhood families in the Industry 4.0 era, where digital media increasingly influences literacy practices at home. Using a descriptive mixed-method design (survey of 30 parents and semi-structured interviews), this study describes how often families engage in bedtime stories, the media they use, and their perceptions of the benefits of this practice. The results show variations in consistency in practice, with 37% of parents doing it regularly (≥3 times per week) and 33% occasionally (1-2 times per week), while 13% reported never doing it. The majority, 60% of parents use printed picture books as their primary medium, followed by digital story videos (30%). Regarding perceived benefits, most parents rated bedtime stories as very beneficial for improving vocabulary and language skills (87%) and strengthening emotional bonds (50%). Interview data reinforced these findings, while highlighting a decline in reading routines due to parental fatigue or limited time (67%) and children’s preference for gadgets (40%) as key challenges. This study implies the need for school-family collaboration, such as providing weekly reading guides, and recommends the development of parent-supported to maintain interactive literacy practices in modern families.